Auditors' Opinions, Discretionary Accruals and Financial Risk: Evidence from Jordan - Ali A. Al-Thuneibat; Tawfiq H. Abdel-Jalil (Journal of Accounting, Business and Management (JABM), 2011)
This study aims at providing evidence concerning the relationship between auditors' opinions, discretionary accruals and financial risk in Jordan. Multiple Regression and Multinominal Logit models were used to test the hypothesis. These models were applied on financial information about discretionary accruals, financial leverage, earnings volatility and auditors' opinions of all Jordanian companies in both industrial and service sectors listed in Amman Bourse (AB) during the period 2002 -2006. The findings of the study showed that there is no significant influence of auditors opinions over discretionary accruals, and there is no significant effect for earnings volatility over the relationship between auditors opinion and discretionary accruals, but there is a significant influence of financial leverage over this relationship. The findings also showed that there is no significant influence of discretionary accruals over auditors opinion, and there is no significant effect for earnings volatility and financial leverage over this relationship. On the basis of the above conclusions, the researchers would recommend that there is an urgent need to improve audit quality in Jordan and enhance the importance of audited financial statements in decision making. Improving audit quality requires a strong regulating system of the audit profession in order to provide a strong mechanism of monitoring the audit firms and the work of the auditors The originality of the study stems from the fact that it provides us with first hand evidence from Jordan as a developing country, about the relationship between auditors' opinions, discretionary accruals and financial risk.